PENGARUH PERENCANAAN PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA DI SEKOLAH: SEBUAH KAJIAN LITERATUR - Rabiatul Adawiyyah; Faizah (Journal Education and Government Wiyata, 2024)
The purpose of this discussion is to examine how the success of student learning outcomes is influenced by teachers' approaches to educating students and to assess the level of professionalism among teachers in Indonesia, particularly in each school. This study employs a literature review method, incorporating relevant research findings. Numerous studies indicate a strong correlation between teaching quality and student achievement. While cognitive outcomes show a significant improvement, affective and psychomotor outcomes also demonstrate notable growth. It is strongly recommended that teachers thoroughly prepare their lessons, as this preparation directly impacts student learning outcomes, aligning with the school's vision and mission, as well as the expectations of students' parents.